2005
DOI: 10.4065/80.12.1623
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Receptor Antagonists in the Medical Management of Chronic Heart Failure

Abstract: The benefits of aldosterone receptor antagonists (spironolactone and eplerenone) for patients with heart failure were shown in 2 recent randomized controlled trials. Some of the proposed mechanisms of action of aldosterone antagonists are (1) inhibition of myocardial and vascular remodeling, (2) blood pressure reduction, (3) decreased collagen deposition, (4) decreased myocardial stiffness, (5) prevention of hypokalemia and arrhythmia, (6) modulation of nitric oxide synthesis, and (7) immunomodulation. Like ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 66 publications
2
13
0
2
Order By: Relevance
“…Evidence also suggests a beneficial effect of aldosterone antagonism in diastolic heart failure by virtue of their beneficial effects on cardiac hypertrophy and fibrosis [148,198]. These findings underscore the critical importance of inhibiting the RAAS in diabetic patients, especially when diastolic dysfunction is present and the process is, at least, partially reversible.…”
Section: Therapeutic Management Of Diabetic Cardiomyopathymentioning
confidence: 94%
“…Evidence also suggests a beneficial effect of aldosterone antagonism in diastolic heart failure by virtue of their beneficial effects on cardiac hypertrophy and fibrosis [148,198]. These findings underscore the critical importance of inhibiting the RAAS in diabetic patients, especially when diastolic dysfunction is present and the process is, at least, partially reversible.…”
Section: Therapeutic Management Of Diabetic Cardiomyopathymentioning
confidence: 94%
“…In addition to a variety of pleiotropic effects (5), eplerenone may exert a diuretic, as well as a potassium (K)-sparing effect. The aim of the present study was to determine whether a diuretic and/or a K-sparing effect could be detected in patients treated with eplerenone in an EPHESUS substudy and, if any, whether these effects influenced cardiovascular outcomes.…”
mentioning
confidence: 99%
“…It has also improved outcomes in patients after myocardial infarction, in those with hypertension, and in those with other highrisk vascular disease-populations that are thought to be at risk for HF-PEF. Inhibitors of the RAAS have been shown to blunt neurohormonal activation in patients with systolic heart failure [40] and thereby decrease salt and water retention, which contributes to symptoms of dyspnea and effort intolerance in patients with heart failure. In an experimental model of hypertension and compensated LVH, it was demonstrated that the blockade of the AT 1 receptor can prevent the development of heart failure [41].…”
Section: Inhibition Of the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%